2007
DOI: 10.1007/s11136-007-9198-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying item response theory (IRT) modeling to questionnaire development, evaluation, and refinement

Abstract: When used appropriately, IRT can be a powerful tool for questionnaire development, evaluation, and refinement, resulting in precise, valid, and relatively brief instruments that minimize response burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
618
0
19

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 660 publications
(651 citation statements)
references
References 51 publications
14
618
0
19
Order By: Relevance
“…IRT is a family of mathematical models that allow researchers to assign unique values (i.e., parameters) to each item based on how likely people with different levels of the measured construct are to endorse reach response category. 21,22 In the current study, the results of each linking method showed a high degree of similarity, consistent with previous reports for the domains of depression 23 , anxiety 24 , and fatigue 25 . Here we report only the results of the fixed IRT calibration, consistent with other published reports.…”
Section: Resultssupporting
confidence: 91%
“…IRT is a family of mathematical models that allow researchers to assign unique values (i.e., parameters) to each item based on how likely people with different levels of the measured construct are to endorse reach response category. 21,22 In the current study, the results of each linking method showed a high degree of similarity, consistent with previous reports for the domains of depression 23 , anxiety 24 , and fatigue 25 . Here we report only the results of the fixed IRT calibration, consistent with other published reports.…”
Section: Resultssupporting
confidence: 91%
“…The relationship between patients' response to an item and their level of disability, here called IRT disability, was modeled as ordered categorical data, and item characteristic curves (ICC) are used to quantify and visualize it (17). Observed scores for each EDSS item were modeled describing the probability of a given score as a function of patients' disability variable using a logistic model:…”
Section: Modeling Methodsologymentioning
confidence: 99%
“…Item Response Theory (IRT) has been reported to be a promising approach compared to the classical methods (5) in the development and validation of tests in patient-reported outcomes (PRO) research (6,7). It has also been extensively used in computerized adaptive educational testing applications (8).…”
Section: Introductionmentioning
confidence: 99%